Relationships between different trends of the Mediterranean diet and cardiovascular disease-related risk factors in China: results from the CHNS study, 1997–2009 - Bao, Zhengyang; Qian, Zhengtao; Chen, Jiale; Chen, Yu; Li, Na; Ye, Yang; Ren, Yongwei; Tang, Yiming; Chen, Daozhen (Frontiers in Nutrition, 2024)
Objectives: The present study aimed to explore the associations of the Mediterranean diet trajectories with cardiovascular disease-related risk factors in Chinese adults. Methods： A total of 4332 participants in The China Health and Nutrition Survey were included in this study. The group-based trajectory model was applied to explore the Mediterranean diet trajectories (MDT). Linear regressions were conducted to assess the association of the Mediterranean diet trajectories with cardiovascular disease-related risk factors. Stratified analyses by gender were also performed. Results：Group 1 (Persistently low MDT, n=292, 6.74%), Group 2 (Descent MDT, n=537, 12.40%), Group 3 (Ascent MDT, n=454, 10.48%), and Group 4 (Persistently high MDT, n=3049, 70.38%) in the total population were found. Compared to the persistently low MDT, Group 2 and Group 4 were both negatively related to low-density lipoprotein cholesterol (Group 2: β=-0.23, 95%CI: 0.-0.36~-0.09, P=0.001; Group 4: β=-0.25, 95%CI: 0.-0.37~-0.14, P<0.001), total cholesterol (Group 2: β=-0.18, 95%CI: 0.-0.32~-0.04, P=0.010; Group 4: β=-0.31, 95%CI: 0.-0.43~-0.19, P<0.001) and uric acid (Group 2: β=-15.16, 95%CI: 0.-28.66~-2.56, P=0.019; Group 4: β=-27.51, 95%CI: 0.-38.77~-16.25, P<0.001) after adjusting for potential risk factors. Only Group 4 had a negative relationship to triglycerides (β=-0.18, 95%CI: 0.-0.34~-0.02, P=0.028) and blood glucose (β=-0.19, 95%CI: 0.-0.37~-0.02, P=0.032). Conclusions：Four MD trajectories were found in the total participants, males and females, which could be summarized as persistently low MDT, ascent MDT, descent MDT, and persistently high MDT. Adherence to high MDT could reduce the level of some CVD-related risk factors. The effect of remote MD on CVD-related risk factors may be greater than the effect of proximal MD.